2016
DOI: 10.18632/oncotarget.13894
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the best anti-colitis medicine: A comparative analysis of current and prospective compounds

Abstract: Ulcerative colitis (UC) is a chronic lifelong inflammatory disorder of the colon, which, while untreated, has a relapsing and remitting course with increasing risk of progression toward colorectal cancer. Current medical treatment strategies of UC mostly focus on inhibition of the signs and symptoms of UC to induce remission and prevent relapse of disease activity, minimizing the impact on quality of life, but not affecting the cause of disease. To date, however, there is no single reliable treatment agent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…The negative control was carried out without primary antibody incubation. Intensity and degree of staining for YAP1 were evaluated independently by two blinded investigators (AC, ZM) as described previously [55]. For each tissue section the percentage of cells with nuclear YAP1 staining was calculated in five randomly chosen areas per sample by each of two independent researchers (AC, ZM).…”
Section: Histology and Immunohistochemical Stainingmentioning
confidence: 99%
“…The negative control was carried out without primary antibody incubation. Intensity and degree of staining for YAP1 were evaluated independently by two blinded investigators (AC, ZM) as described previously [55]. For each tissue section the percentage of cells with nuclear YAP1 staining was calculated in five randomly chosen areas per sample by each of two independent researchers (AC, ZM).…”
Section: Histology and Immunohistochemical Stainingmentioning
confidence: 99%
“…The predominant drug-based therapies used in UC management, such as aminosalicylic acid, corticosteroids, 6-mercaptopurine, azathioprine and cyclosporine give rise to a range of debilitating side effects at various sites, such as skin, eyes and muscle [ 19 , 20 ]. These therapeutic agents also induce bone marrow depletion and disorders in the lungs, liver and pancreas [ 21 23 ]. Additionally, these treatments are not only non-selective, but also impair lifestyle due to repeated use for protracted periods of time [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…More sophisticated approaches based on novel and potent therapeutic agents, such as monoclonal antibodies, protease inhibitors and anti-TNF-α compounds, are also used in UC [ 27 , 28 ] but their use has limitations due to side effects linked to liver damage, heart disease, infection, skin disease and degenerative disorders [ 25 ]. Arguably, the use of biomolecular drug substances offer few advantages, yet inflict toxicity, non-selectivity and a cost burden on patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 4-HNE is known to activate Nrf2 [ 29 ] and is also a marker of inflammation, we probed for this endpoint. Figure 2 A shows induced expression of 4-HNE in the DSS-treated group and its suppression when mice also consumed AG, HAG or PA. We have previously shown that AG and HAG suppress colitis in mice [ 18 , 19 , 21 , 22 , 30 ]. Consistent with our previous findings, AG, HAG, and now PA suppress colitis in DSS-treated mice ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%